Polarimetry of the superluminous transient ASASSN-15lh. Issue 3 (20th August 2020) - Maund, J R; Leloudas, G; Malesani, D B; Patat, F; Sollerman, J; de Ugarte Postigo, A
ABSTRACT: ASASSN-15lh is the intrinsically brightest transient observed to date. Despite being the subject of concerted photometric and spectroscopic observing campaigns, there is still significant debate about the true nature of this transient and the mechanism responsible for its great luminosity. Here we report five epochs of imaging polarimetry and two epochs of spectropolarimetry conducted with the ESO Very Large Telescope (VLT) FOcal Reducer and low dispersion Spectrograph (FORS) polarimeter, spanning +28–91 d (rest frame) with respect to the light-curve maximum. The overall level of polarization across this period is seen to be low ${\sim} 0.5\!-\!0.8 {{\ \rm per\ cent}}$, however at +51.6 d, approximately corresponding to a dip in the ultraviolet (UV) photometric light curve, the polarization is seen to briefly rise to $1.2{{\ \rm per\ cent}}$ in the observed V band. We discuss this behaviour in the context of previous polarimetric observations of superluminous supernovae (SLSNe) and tidal disruption events (TDEs). Although the level of polarization could be consistent with polarization observed for SLSNe, the behaviour around the UV light-curve dip could also be consistent with a TDE observed almost edge on.